Channel catfish and freshwater drum population demographics across four large Midwestern rivers. Issue 1 (30th April 2022) - Whitten, Andrya L.; DeBoer, Jason A.; Berry, Sabina; Moody-Carpenter, Cassi; Lubinski, Benjamin J.; Rude, Neil P.; Chick, John H.; Colombo, Robert E.; Whitledge, Gregory W.; Lamer, James T.
Abstract: Channel catfish ( Ictalurus puncatus ) and freshwater drum ( Aplodinotus grunniens ) are two commercially and recreationally important species in large rivers of the Midwestern United States. Understanding their population demographics is essential to managing sustainable populations. In this study, we determined and compared the size structure, individual growth, and mortality estimates of channel catfish and freshwater drum among the Illinois River and sections of the Mississippi, Ohio, and Wabash rivers to provide a current baseline for managing these populations. Results suggest that both fishes differed in size structure among rivers. Compared to all other rivers, the Mississippi River freshwater drum growth rate was the highest and the theoretical maximum length was the lowest, and the Ohio River annual mortality was lowest. Channel catfish growth did not differ among rivers, but annual mortality was significantly higher in the Mississippi River compared to the Wabash River. Given the importance of these two fishes, better understanding of their population demographics in these systems is essential to improving current and future fisheries management programs.